A STUDY ON CHARACTERISTICS OF A MODERN STRUCTURED PACKING - CHO, SY; LEE, YY; KIM, SJ (KOREAN INST CHEM ENGINEERS, 1995)
The hydraulic characteristics including dry pressure drops, liquid holdups, flooding data, effective interfacial areas, and wet pressure drops of a modern structured packing (Sulzer EX) were studied using the air-water system. As a result, a predictive equation for the wet pressure drops of this structured packing at below the flooding point was derived for the design of the distillation column. The equation was tested with the experimental data obtained from the practical vacuum distillations. It was suggested that the equation is useful for the vacuum distillation under the flooding point, but the deviation is increased above the flooding point.